1169. Derivation And Validation of an International Clinical Prognostication Model for 28-day Sepsis Mortality. (15th December 2022) - Blair, Paul W; Mehta, Rittal; Som, Tin; Okello, Stephen; Tsalik, Ephraim L; Wailagala, Abdullah; Woods, Christopher W; Prouty, Michael; Chenoweth, Josh; Letizia, Andrew; Faix, Dennis; Adams, Nehkonti; et al.
Abstract: Background: Survival prediction models have largely been derived and validated only in high-resource Western countries or in single center studies. We sought to create a prediction model for 28-day mortality using laboratory and physiologic parameters from 3 international sepsis cohorts and externally validated the model. Methods: During 2014 to 2021, adult hospitalized patients with suspected infection were enrolled in Durham, United States (N=180) and those with suspected infection and ≥2 SIRS (Systemic Inflammatory Response Syndrome) criteria in Takeo, Cambodia (N=200), and Kumasi, Ghana (N=187). Twenty-five clinical laboratory and physiologic parameters were candidate covariates and sepsis screening scores included as comparators. First, bivariate Cox regression models were performed to determine risk of individual parameters. Then, a 10-fold cross-validated forward stepwise model selection technique was used to eliminate nonsignificant variables using a p-value < 0.10 and the cross-validated C-statistic was estimated. Lastly, this model was applied to an external cohort of hospitalized adults with suspected infection and ≥2 SIRS in Fort Portal, Uganda (N=331 with 9.3% 28-day mortality). Results: Among 567 participants, overall mortality was 16.4% at 28-days. Mortality rate highest in Ghana (31.0%), followed by Cambodia (11.0%) and the United States (7.2%). Bivariate analyses identified hypernatremia ( >145 mEq/L) being associated with the highest risk of death (hazard ratio: 7.42; 95% CI: 3.65 to 15.10; Figure 1). On multivariable analysis, a 28-day mortality model including mean arterial pressure, Glasgow Coma score, blood sodium, lactate, and blood urea nitrogen (Table 1) resulted in a 10-fold cross-validated C-statistic of 0.80 (95% CI: 0.61 to 0.88). This model predicted mortality accurately in the validation cohort with a C-statistic of 0.74 (95%CI: 0.69 to 0.79). Figure 1. Forest plot for bivariate analyses for one month survival across United States, Cambodia, and Ghana cohorts. Conclusion: Hypotension, altered mental status, serum sodium, serum BUN, and plasma lactate accurately identified risk of death by 28-days among those with suspected sepsis in 3 international derivation cohorts and in a validation cohort in Uganda. Our findings emphasize the importance of clinical laboratory results for sepsis risk stratification. Disclosures: Ephraim L. Tsalik, MD PhD, Danaher Diagnostics, Predigen, and Biomeme: In the past 3 years, I have had held equity and consulted for Predigen and Biomeme. Currently, I am an employee of Danaher Diagnostics. Christopher W. Woods, MD MPH, Predigen, Inc: Co-founder.